Differences in Effectiveness Between Lemongrass Plus Ginger and Lemon Plus Honey To Reduce Morning Sickness - Megawati Megawati; Abela Mayunita (Global Health Science Group, 2023)
Nausea and vomiting are normal in pregnant women. However, this condition will change if sustained with a high quantity in a day, so it can disrupt nutritional balance, electrolyte fluids, and can affect the quality of pregnancy. Anti-nausea drugs sometimes can not work effectively when pregnant women continuously vomit, one of the nonpharmacological therapies. The purpose of this study was to measure the effectiveness of ginger drink plus lemongrass compared to lemon plus honey on reducing morning sickness symptoms in pregnant women. This research is a type of intervention research with experimental quasy design. The location used for this research is in the working area of the Bandung Health Center, Serang Regency, Banten Province in May – June 2023. The sample used in this study used a total sampling of 32 pregnant women. Sample selection with purposive sampling techniques. Statistical analysis using independent t test. The results of the independent t test for ginger + lemongrass were p value 0.028 < 0.05, while the test results for lemon honey were p value 0.048 < 0.05 it can be concluded that giving ginger and lemongrass water as well as lemon and honey has an effect in reducing morning sickness and is statistically significant